OP0287-HPR Systemic Sclerosis Patients with Digital Ulcers Report Impaired Physical Function during an Annual Follow Up. (10th June 2014) - Garen, T.; Hoffmann-Vold, A.-M.; Midtvedt, Ø.; Andersson, H.; Gunnarsson, R.; Bruaset, H.; Fresjar, K.; Palm, Ø.
Abstract : Background: Systemic sclerosis is a rare connective tissue disease were clinical symptoms depend upon the disease subtype and the distribution of organ involvement. This chronic disease has often a relapsing course with substantial effects on function leading to impaired daily activities. Objectives: To describe changes in self reported symptoms and disability in systemic sclerosis patients, and secondly to assess correlations between disease manifestations and changes. Methods: Scleroderma patients included in the "The Norwegian Systemic Connective Tissue Disease and Vasculities Registry" (NOSVAR) were studied. All the patients fulfilled the 2013 ACR/EULAR SSc criteria. At each visit patients undergo a physical examination and were asked to complete self reported questionnaires. The HAQ-DI was applied to measure patients function (dressing, arising, eating, walking, hygiene, reach, grip and common daily activities) scored from 0-3 were a HAQ-DI of >1.0 were considered as high (low function). Patients self reported symptoms were measured by five VAS-scales (15cm) where the domains address severity of overall disease activity, Raynaud's phenomenon, discomfort by finger ulcers, breathing and intestinal problems. Disease characteristic and gastrointestinal symptoms were tested for correlation with changes. The patients first and last self reported questionnaires assessments were compared. Disease duration was defined as the time from diagnosis to the first registration. Wilcoxon Signed Rank Test was applied to describe changes. Pearson correlation tests were used to explore associations. The effect size was calculated (Choen). A value of 0.20-0.49 represented a small change, 0.50 -0.79 a medium change and ≥0.80 a large change. Mean change was presented as average annual change. Results: A total of 182 SSc patients (87% women), mean (SD) age (SD)57 (12), median (25th, 75th) disease duration 4, 5 (1, 6, 8, 5), diffuse (25%) and limited SSc (72%) completed at least two assessments of the self reported questionnaire HAQ-DI and self reported symptoms. Patients had a baseline median (25th, 75th percentile) HAQ-DI of 0, 47 (0, 22, 0, 77), Raynaud's phenomenon, 0.84 (0.40, 1, 40), Finger ulcers, 0.10 (0, 0, 40) Overall disease activity 0, 72 (0, 25, 1, 40), Intestinal problems 0, 26 (0.02, 1, 1) and Breathing 0, 34 (0, 08, 1, 31).Overall mean change after a median follow up of 6.2 years in HAQ-DI and patients self reported finger ulcers was, -0, 07 (p=0.014) and -5.94 (p=0.019), respectively. The average annual change was mean (SD) -0.1031 (0.81) estimated to r= -0.23 for HAQ-DI and mean (SD) r=-0.60 for the finger ulcers, indicating impaired function with time. No correlation with HAQ changes and disease characteristics listed and gastrointestinal symptoms were found. Changes in complaints of finger ulcers correlated with and change in MHAQ (B -0.229, p=0.006). Digital ulcers correlated with patients reported finger ulcers at first visit but not with changes (B -0.228, p=0.005) Conclusions: Physical function and self reported discomfort by finger ulcers declined during follow up. Progression of disability correlated with changes in self reported finger ulcers. Increased attention from health professionals including physicians to prevent and treat digital ulcers may have a favourable impact on patient's physical function in daily life. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4970